Farmers’ Perspectives on Biotechnology Innovation on a New Cassava Variety in Tamil Nadu - Guilani, Alessandra; Ashok, K R; Wyss, Rahel; Zbinden, Karin (JOURNAL OF ROOT CROPS, 2017)
Cassava ( Manihot esculenta Crantz) is a highly productive tuber crop growing on marginal land, providing rural communities in India with nutritious food, as well as income generated by huge industrial demand for sago and starch. In Tamil Nadu (TN) alone it supports over 10,000 smallholder farmers. To sustain the livelihoods of this community of smallholder farmers, the Indo-Swiss Collaboration in Biotechnology (ISCB) works towards cassava virus (i.e. Cassava Mosaic Disease) resistant varieties. Socio-economic partners collaborate with biotechnologists to support ISCB Cassava project’s objectives of improving food security and rural development, by supporting development of biotechnological products according to end users’ perspective (i.e. smallholder farmers and other value chain players). Using a combination of qualitative participatory research methods, this study addresses the needs and constraints of the farmers and other players, related to the cassava planting material system in the cassava industrial production area of Dharmapuri, Namakkal and Salem districts of Tamil Nadu. By understanding farmers’ and other players’ needs, will make the innovation more likely to be adopted. Moreover, the research aims at creating a network of public and private partners to rely on for the dissemination of innovations. In an area where cassava is largely produced for starch and sago, farmers seem mainly concerned about varieties with high yield and high starch content, shape and colour. In order to assure farmers acceptance of a new variety to be introduced, the yield and starch content should be as high as, or greater than the varieties currently in use. Though cassava planting material is available and affordable, when a new variety is released, the current planting material distribution strategy seems to be inadequate for market penetration. Socio-economists and biotechnologists agree on the fact that market-oriented distribution strategy needs to be further analysed and built, by including other players from the private and public sector.